The Ethics of Organizations: A Longitudinal Study of the U.S. Working Population - Kaptein, Muel (Journal of business ethics, 2010)
The ethics of organizations has received much attention in recent years. This raises the question of whether the ethics of organizations has also improved. In 1999, 2004, and 2008, a survey was conducted of 12,196 U.S. managers and employees. The results show that the ethical culture of organizations improved in the period between 1999 and 2004. Between 2004 and 2008 unethical behavior and its consequences declined and the scope of ethics programs expanded while ethical culture showed no significant improvement during the same period. The article concludes with a discussion of the implications of these findings for future research and practice.